Maxillary labial frenum and simple V-plasty technique of frenectomy - AA Khoshkhonejad (Tehran University of Medical Sciences, 1993)
Frenum or Frenulum is defined by Miller as a membrane joining two parts that causes movement limitation. Oral cavity frenums are : 1) labial frenums of maxilla and mandible which are also known as inhibition of lips. 2) lingual frenum of tongue located between central incisors 3) frenum in mandibular premolar area. Frenum can be one or double layered. If The attachment located in gingival line and alveolar mucosa and attached gingival, no complication is anticipated while higher locations to free gingival directions, it would be a high frenum that can cause periodontal and orthodontic complications and treatment relapse. Complete evaluation on bone destructions in central incisors area, diasthema and teeth mobility related to frenum should be carried out.